Penerapan Permainan Puzzle Untuk Perkembangan Emosi Kognitif Dan Kemampuan Motorik Halus Pada Anak - Sri Utami Asmarani; Syffa Yunia Istiqomah; Rosalinda Diana Adawiyyah; Resa Optiana; Nuranti Nuranti (Yayasan Inspirasi El Burhani, 2023)
Introduction: Early childhood education is a coaching effort for children aged birth up to six years. This is done by providing educational stimulation from an early age in order to optimize the growth and development of children so that they are ready to continue to the next level of education. At that age, children must be given a stimulus for maximum and optimal development in both motor, cognitive and social-emotional development. Objective: The purpose of this community service is to find out the effectiveness of puzzle games on the development of emotional, cognitive and fine motor skills in children at Kenanga 2 Early Childhood Education in Banjar City. Method: As an effort to determine the effectiveness of the application of puzzle games in an effort to improve emotional, cognitive and fine motoric development in children in Kenanga 2 Early Childhood Education Kota Banjar with a total of 16 respondents using observational research methods with puzzle game media. The 16 respondents were divided into 4 groups, with each group being given 40 minutes to complete the puzzle. Result: The results of the observations made showed that 11 children had good emotions (68.75%) and 5 people (31.25%) had emotional problems, 1 person (6.25%) had cognitive problems and 15 people (93.75%) had cognitive abilities good fine motor. Conclusion: This community service has a positive value for the students of Banjar City Kenanga 2 Early Childhood Education. This can be seen from the enthusiasm and activeness of the audience or participants in carrying out puzzle game activities and the results of observations made have a good value on emotional, cognitive status and on fine motor skills in children.